Assessing the Importance of Non-Necrotising Granulomatosis - Alende-Castro, Vanesa (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Objective: The diagnosis of non-necrotising granulomatosis (NNG) is very frequent in clinical practice. There are few studies, however, within the spectrum of pathologies that cause NNG; consequently, except for sarcoidosis, little information is available. The objective is to determine the prevalence of sarcoidosis, autoimmune diseases and other entities in NNG. Methods: We collected all pathological reports with a diagnosis of non-necrotising granulomatosis from 1 January 2010 to 31 December 2014 in the Clinical University Hospital of Santiago de Compostela, Spain. Results: A total of 290 tissue samples from 207 patients were reviewed. Of these patients, 50.7% were women, with a mean age of 51.2 years. The origins of the samples were: skin 32.9%, lymph nodes 26.6%, transbronchial biopsy 14.5%, lung 5.8% and others 20.2%. Final diagnoses were: sarcoidosis 59.9%; infectious diseases 7.7%, including tuberculosis 4.0% and non-tuberculous mycobacterial infection 1.4%; foreign body granulomatosis 6.3%; neoplasms 5.9%; autoimmune disease 3.1% and others 4.0%. A diagnosis was not determined in 5.9% patients. Conclusion: The prevalence of sarcoidosis in NNG is over 50%, while autoimmune disease prevalence is considerably lower (3.1%), with Wegener granulomatosis being the most commonly reported. The most frequent alternative diagnosis was infectious disease, mainly tuberculosis. But it is important to keep the possibility of malignancy in mind. An accurate diagnosis is possible in the majority of cases.